Influence of Water Salinity on the Growth and Survivability of Asp Larvae Leuciscus aspius (Linnaeus, 1758) under Controlled Conditions - Roman Kujawa; Przemysław Piech (Animals, 2022)
The effect of water with a salinity 3, 5, 7, 9 and 11 ppt on the growth and survivability of asp Leuciscus aspius (L.) larvae was investigated. A control sample consisted of asp larvae reared up in freshwater (0 ppt). Larvae were fed for 21 days with nauplii of the brine shrimp Artemia salina. Water salinity was observed to have a considerable effect on the growth and survivability of asp larvae. In addition, saline water extended the life span of Artemia salina nauplii, which resulted in their prolonged availability to asp larvae. Asp larvae showed low tolerance to the salinity of water, reaching 9–11 ppt. Depending on the degree of salinity, the mean final weight of larvae varied from 122.6 to 139.4 mg, at body lengths from 23.8 to 25.6 mm, respectively. The best body length increments were recorded among asp larvae maintained in water with a salinity of 3 ppt. Depending on the level of water salinity, the final survivability of asp larvae ranged from 16.9 to 94.5%. The highest and increasing mortality was demonstrated among the larvae reared in water of the salinity equal to 11 ppt. It is not recommended to rear asp larvae in water with a salinity above 7 ppt due to the low survivability and large differences in the body size of the larvae that managed to survive.